Pelatihan Peduli Kebersihan Lingkungan Secara Berkelanjutan di Kelurahan Wawanggu Kecamatan Kadia Kota Kendari - Tanzil; Peribadi; Bauto, La Ode Monto; Rusli, Muhammad; Sarmadan; Umran, Laode Muh. (CV. Literasi Indonesia, 2022)
The purpose of this community service activity is to increase public knowledge about the causes of unclean environmental problems in urban areas and to make efforts to prevent various problems related to environmental hygiene problems. The implementation of this service is carried out in two stages; first counseling/training. In the first stage, the instructor provides lessons to the trainees. The trainer encourages all participants to raise various environmental hygiene issues in their area. Furthermore, the trainer interacts directly with the residents to understand the problems they are facing. In this service, a Focus Group Discussion (FGD) was also held with government officials and community leaders in the Wawanggu village. With this activity, community groups that care about the realization of environmental cleanliness have been carried out. These community groups are trained to handle various environmental hygiene issues, for example using waste into a product that has economic value. This activity is integrated with the Work Program of the Neighborhood Association (RT) in the service activity area so that there is mutual strengthening between community members and village government officials.